Anti-viral activity of Phyllanthus niruri against hepatitis C virus - Tutik Sri Wahyuni,; Dzul Azmi,; Adita Ayu Permanasari,; Myrna Adianti,; Tumewu, Lydia; Tri Widiandani,; Utsubo, Chie Aoki; Aty Widyawaruyanti,; Achmad Fuad,; Hotta, Hak (Penerbit Universiti Kebangsaan Malaysia, 2019)
Hepatitis C virus (HCV) infection is a global problem that causes liver disease and hepatocellular carcinoma. Although the current standard treatment provided a significant improvement on response rate with sustain virology response more than 90%, however, the high cost was remaining limited access to this therapy, resistance emergence and serious side effects which provide the necessities to find the new anti-HCV agents. The current study, we evaluated the ethanol extract of Phyllanthus niruri for its anti-HCV activities. Anti-HCV activity was determined by in vitro culture cells of Huh 7it. Anti-HCV activity of P. niruri extract revealed strong inhibition against HCV with IC50 values of 4.14 µg/mL and yield stronger activity in the entry step of the HCV life cycle. Moreover, the P. niruri extract enhanced anti-HCV activity of simeprevir (NS3 protease inhibitor) with increase the activity up to 4-fold compared to a single treatment of simeprevir. Docking analysis was performed to predict the interaction phyllanthin and hypophyllantin, known compounds of P. niruri against HCV receptor. Both of phyllantin and hypophyllantin were mediated a strong interaction with 4GAG, a protein that involved in entry step of HCV. These results suggested that the ethanol extract of P. niruri may be good candidates for the development of anti-HCV drugs.